IMPLEMENTASI NILAI RELIGIUS DALAM PENDIDIKAN KARAKTER BERBASISSUNNAH RASULULLAH - Dwi Sukmanila Sayska (Universitas Islam Negeri Sumatera Utara Medan, 2017)
This study aimed to describe and analyst the implementation of religious values in character education based on sunnah Rasulullah in SD IT An-Najah Takengon. This research uses descriptive qualitative approach. Data collection was carried out through observation, interviews, and documentation. Data analysis techniques include the collection of data, data presentation, data reduction, as well as the withdrawal of the conclusion. The results of this research show that there are implementation of religious values in character education based on sunnah Rasulullah in SD IT An-Najah Takengon. The implementation is done in various activities at the school, and its is: (1) instilling tawheed and Islamic faith, (2) establishing zhuhr prayer in concregation, (3)memorizing the Holy Quran dan hadeeth (4) wearing islamic dress code especially hijab for girls (5) separating classroom for boys and girls, (6) avoiding in using human doll or animals doll and its paint, and (7) practicing islamic ethic and attitude in daily life.